(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the ghazals of Jafar Muhammad (Jafar Kholmuminov) the themes of love are depicted and the love is turned into an object of relationship. In his ghazals, Jafar Muhammad expresses and describes the lyrical protagonist - the inner feelings and inner feelings of the lover.using the art of analogy through expressions made with the participation of the word creates several images that we can call images of love. We conventionally divide these images into two types, images representing places of love and images representing the means of love.